Social Consciousness in Prose Poems of Pakistani Women Poets - Amina; Tayib, Tahir Abbas (sourcecoder, 2024)
Life’s complexities, challenges, and realities have been extensively explored in Urdu poetry. Female poets have played a pivotal role in driving the poetic revolution through their creative expressions. In order to address broader social Consciousness, intellectual concepts, and revolution, the poet has chosen Nazm instead of Ghazal as Nazm provides freedom to explore subjects in depth, creating an interconnected flow of ideas and themes in combined couplets. Female poets of Pakistan have tried to enlighten every aspect of life in their poetry whether it is social, cultural, religious or feminism conflicts or issues with their abilities to create an impact-full literary works through imaginative and symbolic expressions. They have tried their best to address these issues on national and international platforms. Female poets of Pakistan have incorporated various topics of life including ups and downs of life, society issues, religious cultures and cultural revolutions in their poetry. Moreover they have also addressed feminism in their poetry highlighting the injustice and unequal rights in their poetry. These topics are not just a source of great attention but also makes them unparalleled and distinctive from other female poets.